2017
DOI: 10.15448/1980-6108.2017.1.25082
|View full text |Cite
|
Sign up to set email alerts
|

Does neuromuscular exercise training improve proprioception in ankle lateral ligament injury among athletes? Systematic review and meta-analysis

Abstract: Aims:The prevalence rate of ankle complexities is increasing at a constant rate among athletes. This study aimed to systematically describe the facts and findings related to the effectiveness of training programs on proprioception among athletes suffering from ankle ligament injury. Methods: A literature search in online libraries ( Google Scholar, PubMed, EBSCOhost, and ProQuest) using different search engines was conducted for the systematic review and meta-analysis. The common keywords included NEUROMUSCULA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Several overlapping systematic reviews have found evidence supporting the effectiveness of neuromuscular training, 34 , 35 , 250 proprioception and balance training, 25 , 34 , 48 , 143 , 197 and exercise interventions 50 , 83 for preventing ankle injuries. Four overlapping systematic reviews 25 , 48 , 116 , 197 found that proprioception or balance training reduced ankle injuries by 31% to 46%, and these training programs primarily consisted of single-leg stance challenges, wobble/balance board exercises, and sport-specific agility drills. Furthermore, Schiftan et al 197 found that proprioceptive training (ie, balance exercise with or without balance/wobble board or ankle disc for at least 8 weeks) was effective at reducing ankle sprains in athletes with (RR, 0.64; 95% CI, 0.51-0.81) and without (RR, 0.57; 95% CI, 0.34-0.97) a history of ankle sprain.…”
Section: Resultsmentioning
confidence: 99%
“…Several overlapping systematic reviews have found evidence supporting the effectiveness of neuromuscular training, 34 , 35 , 250 proprioception and balance training, 25 , 34 , 48 , 143 , 197 and exercise interventions 50 , 83 for preventing ankle injuries. Four overlapping systematic reviews 25 , 48 , 116 , 197 found that proprioception or balance training reduced ankle injuries by 31% to 46%, and these training programs primarily consisted of single-leg stance challenges, wobble/balance board exercises, and sport-specific agility drills. Furthermore, Schiftan et al 197 found that proprioceptive training (ie, balance exercise with or without balance/wobble board or ankle disc for at least 8 weeks) was effective at reducing ankle sprains in athletes with (RR, 0.64; 95% CI, 0.51-0.81) and without (RR, 0.57; 95% CI, 0.34-0.97) a history of ankle sprain.…”
Section: Resultsmentioning
confidence: 99%